2012
DOI: 10.1016/j.oraloncology.2011.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial derived factors inhibit anoikis of head and neck cancer stem cells

Abstract: Recent evidence demonstrated that cancer stem cells reside in close proximity to blood vessels in human head and neck squamous cell carcinomas (HNSCC). These findings suggest the existence of a supporting perivascular niche for cancer stem cells. Objective The purpose of this study was to evaluate the effect of endothelial cell-secreted factors on the behavior of head and neck cancer stem-like cells (HNCSC). Materials and methods HNCSC were identified by sorting UM-SCC-22A (cell line derived from a primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 31 publications
0
31
0
4
Order By: Relevance
“…13,25,41,42 Our current data indicate that tumor cells grown as orospheres (a condition that favors CSC growth) were highly positive for sLeX compared to their adherent counterpart; even the sLeX- orospheres became 100% sLeX+ within few days. Floating orospheres were strongly positive for CD44 and ALDH confirming sLeX preferential expression in CSC.…”
Section: Discussionmentioning
confidence: 62%
“…13,25,41,42 Our current data indicate that tumor cells grown as orospheres (a condition that favors CSC growth) were highly positive for sLeX compared to their adherent counterpart; even the sLeX- orospheres became 100% sLeX+ within few days. Floating orospheres were strongly positive for CD44 and ALDH confirming sLeX preferential expression in CSC.…”
Section: Discussionmentioning
confidence: 62%
“…CSCs reside in close proximity to blood vessels and can give rise to tumor endothelium (24). It was reported that endothelialderived factors inhibit anoikis of ALDH + CD44 + head and neck cancer stem cells (25). EMT is regarded a necessary process that empowers CSCs to disseminate from primary tumors and to seed metastases.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that UM-SCC-22B contains a sub-population of cells that exhibit cancer stem-like characteristics. 160 Photomicrographs (200x) of UM-SCC-22B cells cultured with serum-free medium in ultra-low attachment plates in presence of 0 or 50 ng/ml EGF for 5 days. The formation of spheroid-like colonies containing at least 25 cells (named orospheres) was enhanced by EGF treatment.…”
Section: Figurementioning
confidence: 99%